PENDAMPINGAN LITERASI MELALUI AKTIVITAS MENDONGENG DAN BERMAIN PUZZLE - Nande, Marsel; Meke, Konstantinus Denny Pareira; Naga, Marianus Kejapilus; Woe, Emerensiana; Putri, Elma Silvia Dei (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
The community service program aims to improve literacy skills and develop a culture of numeracy literacy in the home environment through reading houses. The form of community service activities is carried out through counselling or education on the importance of literacy for students through storytelling activities and playing picture puzzles. The community service program is carried out collaboratively by a group of lecturers and students and reading house volunteers and companions in the Nanganesa area, Ende Regency. Implementation of activities goes through several stages, namely planning, determining technical implementation, program implementation and evaluation. The results of community service have succeeded in improving children's literacy skills through storytelling activities and playing puzzles. It is hoped that they can implement them in the school environment.